2018
DOI: 10.4038/cjs.v47i2.7516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different vase solutions on postharvest longevity of cut foliage <i>Ophiopogon</i> <i>japonicus</i>

Abstract: To investigate the function of BAP, amount of chlorophyll was quantified using leaf pigment extracts. The vase life of O. japonicus could be extended from 5.1 days to 12.5 days by giving BAP based vase solutions. Chlorophyll contents of leaves dipped in BAP solutions were significantly higher than the control (distilled water). CuSO 4 solutions did not show any significant antibacterial effects compared to the control. According to vase life data, the most effective vase solutions were CuSO 4 .5H 2 O (0.5 mM),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Third day in vase log 10 cfu mL This observation is comparable to other experiments in which the biocidal influence of preservatives and pulsing agents inhibit microbial proliferation in the stems and/or vase water of many cut flower and foliage plant species (Naing et al, 2017;Wijayabandara et al, 2018). As shown in Tables 1, 2 and 3, wet cold storage duration significantly affected microbial proliferation (P˂0.0001) in the vase water of the spikes pulsed with 600 ppm 8-HQS plus 5% sucrose solution compared with the control.…”
Section: Days Of Storagesupporting
confidence: 79%
“…Third day in vase log 10 cfu mL This observation is comparable to other experiments in which the biocidal influence of preservatives and pulsing agents inhibit microbial proliferation in the stems and/or vase water of many cut flower and foliage plant species (Naing et al, 2017;Wijayabandara et al, 2018). As shown in Tables 1, 2 and 3, wet cold storage duration significantly affected microbial proliferation (P˂0.0001) in the vase water of the spikes pulsed with 600 ppm 8-HQS plus 5% sucrose solution compared with the control.…”
Section: Days Of Storagesupporting
confidence: 79%
“…8-HQS controlled microbial growth in the holding solution and helped to prolong vase life of cut stems (Hettiarachchi and Balas, 2005). The enhancement of vase life of cut foliages by using sucrose in combination with AgNO 3 @ 20 and 40 ppm reported by Malakar et al, 2017. Wijayabandara et al, 2018 reported that the most effective vase solutions for Ophiopogon japonicus were sucrose 20 or 30 g/L pulsing treatments for 24 hour.…”
Section: Resultsmentioning
confidence: 99%
“…is a valuable medicinal herb used in the pharmaceutical industry as a tonic, cosmetic, or medicinal product to treat diseases such as cough, oligogalactias, urine retention, or diabetes. Besides, it is considered an ornamental plant (Wijayabandara et al, 2015) or an intercropping plant to cover the soil and limit weeds and fungal diseases (Iqbal et al, 2004;Lin et al, 2009). In Vietnam, it has been grown as an intercropping crop with perennial orchards and industrial crops (Nguyen and Nguyen, 2011).…”
Section: Introductionmentioning
confidence: 99%